2017
DOI: 10.1002/ana.24826
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in noncoding RNA RNU12 causes early onset cerebellar ataxia

Abstract: Interference with particular spliceosome components, including small nuclear RNAs, cause reproducible uniquely distributed phenotypic and transcript-specific effects, making this an important category of disease-associated mutation. Our approach to differential expression analysis of minor intron-containing genes is applicable to other diseases involving altered transcriptome processing. ANN NEUROL 2017;81:68-78.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 30 publications
0
72
2
Order By: Relevance
“…Similarly, mutations in the minor spliceosome U4atac snRNA gene in humans result in splicing defects and the rare disorder microcephalic osteodysplastic primordial dwarfism type I (MOPD1) [30, 57]. Mutations in another minor spliceosome snRNA, RNU12 , result in U12-type exon retention and are associated with cerebellar ataxia[31]. Therefore, a toxic effect of the accumulation of misprocessed UsnRNAs on the spliceosome in response to INTS8 mutations is possible and could result in the differential splicing patterns that we observed in patient versus control cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mutations in the minor spliceosome U4atac snRNA gene in humans result in splicing defects and the rare disorder microcephalic osteodysplastic primordial dwarfism type I (MOPD1) [30, 57]. Mutations in another minor spliceosome snRNA, RNU12 , result in U12-type exon retention and are associated with cerebellar ataxia[31]. Therefore, a toxic effect of the accumulation of misprocessed UsnRNAs on the spliceosome in response to INTS8 mutations is possible and could result in the differential splicing patterns that we observed in patient versus control cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutations in the mouse Rnu2-8 , coding for U2 snRNA, result in cerebellar degeneration [29], RNU4atac mutations in humans result in extreme microcephaly [30] and mutations in RNU12 have been found associated with early-onset cerebellar ataxia[31]. Recently, mutations in the non-canonical deadenylase TOE1 that trims the 3’ ends of pre-UsnRNA, have been linked to pontocerebellar hypoplasia[32].…”
Section: Introductionmentioning
confidence: 99%
“…There are several instances where defects in minor class splicing impact on the developing and adult central nervous system. For example, mutations in the RNU12 gene cause congenital cerebellar ataxia characterized by delayed motor milestones in development, mild learning dif-ficulties and hypotonia in infancy (Elsaid et al 2017). Interestingly, the impaired expression of the CULIN1, ATAXIN10, and SLC9A6 genes, which all contain a U12type intron, has been implicated in several cerebellar ataxia-related phenotypes.…”
Section: Relevance Of Rnpc3 Mutations To Minor Class Splicing Clinicamentioning
confidence: 99%
“…For instance, germline mutations in the gene RNU4ATAC, which encodes the U4atac snRNA, have been linked to the diseases microcephalic osteodysplastic primordial dwarfism type 1 (MOPD1), Roifman syndrome and Lowry-Wood syndrome (Edery et al, 2011;Farach et al, 2018;He et al, 2011;Merico et al, 2015). Moreover, mutations in RNU12 have been associated with an early-onset form of cerebellar ataxia (Elsaid et al, 2017). Finally, mutations in RNPC3, one of the minor spliceosome-specific proteins, have been linked to isolated growth hormone deficiency (IGHD) (Argente et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…inhibition of the minor spliceosome. Transcriptomic analyses of peripheral blood mononuclear cells (PBMCs) from individuals with IGHD, cerebellar ataxia, MOPD1 and Roifman syndrome have revealed that this inhibition of the minor spliceosome results in elevated levels of retention of a subset of minor introns (Argente et al, 2014;Cologne et al, 2019;Elsaid et al, 2017;Merico et al, 2015). Despite a great degree of overlap in the MIGs that are affected in individuals with MOPD1 and Roifman syndrome, there is also a subset of MIGs that are only affected in one condition (Cologne et al, 2019).…”
Section: Introductionmentioning
confidence: 99%